2019
DOI: 10.15537/smj.2019.1.23475
|View full text |Cite
|
Sign up to set email alerts
|

Is prilocaine safe and potent enough for use in the oral surgery of medically compromised patients

Abstract: Objectives: To investigate the potency and speed of action of 2% lidocaine and 3% prilocaine for upper teeth extractions. Methods: This prospective clinical study was conducted from November 2016 to May 2017. Ninety-six patients, aged between 16 to 70 years old were recruited in this study. Two regimens were randomly administered over one visit. Patients, treatment group I, received 2% lidocaine with 1:00.000 adrenaline. Patients treatment group II received prilocaine 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Ozkiriş et al investigated the efficacy of 3 local anesthetic in their study, and showed that lidocaine whose effect started rapidly, was less effective than bupivacaine and ropivacaine which were long-acting after the 8th hour 14 . It has been reported that the duration of action of prilocaine in dental procedures starts faster than lidocaine 15,16 . In our study, a significant decrease was found in the prilocaine group, especially in pain during the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Ozkiriş et al investigated the efficacy of 3 local anesthetic in their study, and showed that lidocaine whose effect started rapidly, was less effective than bupivacaine and ropivacaine which were long-acting after the 8th hour 14 . It has been reported that the duration of action of prilocaine in dental procedures starts faster than lidocaine 15,16 . In our study, a significant decrease was found in the prilocaine group, especially in pain during the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge and training on the management of dental chair medical emergency problems is considered a main source of anxiety affecting not only patient's perception but also all junior and senior dental practitioners [7][8][9][10][11]. Therefore, a successful dental school is the one that has competent clinical trainers who contribute to students' relevant professional development [8][9][10][11][12]. By establishing such an action, a competent dental student and trainer will be able to treat and safely handle any dental chair medical emergency condition with a minimal level of anxiety [7].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency extraction can be carried out for a patient with blood glucose ≤234 mg/dl, has a painful mobile tooth on condition that LA without adrenaline must be administrated and a course of amoxicillin 500 mg for 5 days must be given after extraction (Gazal, 2019, Gazal et al, 2018, Byakodi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%